Conditions and Strategy for Anxiety in Health Workers at Pandemic Covid-19 - Rina Tri Handayani; Suminanto Suminanto; Aquartuti Tri Darmayanti; Aris Widiyanto; Joko Tri Atmojo (Jurnal Ilmu Keperawatan Jiwa, 2020)
The lack of focus to attention on the mental health of health workers has the potential to disrupt or even kill health services and will affect the handling of the Covid-19 pandemic. Anxiety is an early symptom of psychological disorders and is still very likely to be overcome. The purpose of this systematic review is to provide information on conditions and strategies for handling anxiety in health workers during the Covid-19 pandemic. 13 of 106 articles that met the qualitative requirements from various databases such as: Pubmed, Web of Science, Google Scholar, and Elsevier published between 2019-2020. Keywords for this review include: "COVID 19 and Anxiety and Health workers" and "COVID 19 and anxiety and strategy", "COVID 19 and anxiety and Health workers and strategy" and "COVID 19 and anxiety and programs to soThe lack of focus to attention on the mental health of health workers has the potential to disrupt or even kill health services and will affect the handling of the Covid-19 pandemic. Anxiety is an early symptom of psychological disorders and is still very likely to be overcome. The purpose of this systematic review is to provide information on conditions and strategies for handling anxiety in health workers during the Covid-19 pandemic. 13 of 106 articles that met the qualitative requirements from various databases such as: Pubmed, Web of Science, Google Scholar, and Elsevier published between 2019-2020. Keywords for this review include: "COVID 19 and Anxiety and Health workers" and "COVID 19 and anxiety and strategy", "COVID 19 and anxiety and Health workers and strategy" and "COVID 19 and anxiety and programs to solve" and "COVID 19 and anxiety and review". Risk factors for anxiety include: sociodemographic, high working hours, stigma, and concerns exposed to Covid-19. Some steps can be considered including: forming a support group in an effort to resolve anxiety (battle budies), providing counseling services, and coping training.lve" and "COVID 19 and anxiety and review". Risk factors for anxiety include: sociodemographic, high working hours, stigma, and concerns exposed to Covid-19. Some steps can be considered including: forming a support group in an effort to resolve anxiety (battle budies), providing counseling services, and coping training.